Komunikasi Keluarga Beda Budaya dalam Membina Keharmonisan Rumah Tangga Kecamatan Kedondong Kabupaten Pesawaran - Aji Suprapto, Muhamad; Khairullah, Khairullah; Rojiati, Umi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze daily communication patterns and conflict management strategies among intercultural couples in Kedondong District, Pesawaran Regency. The research is motivated by the increasing number of intercultural marriages, which often involve differences in language, customs, and social role expectations within families. A qualitative approach was employed, using in-depth interviews with intercultural couples as the primary data collection method. The findings indicate that couples tend to adopt accommodative communication patterns through the use of a neutral language, metacommunication, and the formation of a “third culture” resulting from the negotiation of cultural values. Conflict management is primarily conducted through integration and compromise strategies, supported by responsive tolerance manifested in respect for expressive differences, self-directed cultural learning, and the role of spouses as mediators with extended families. These results suggest that responsive tolerance is a key factor in maintaining harmony and sustainability in intercultural family relationships.